1998
DOI: 10.1055/s-2007-1000152
|View full text |Cite
|
Sign up to set email alerts
|

Selective Neutrophil Depletion with Monoclonal Antibodies Attenuates Ischemia/Reperfusion Injury in Skeletal Muscle

Abstract: The purpose of this study was to determine whether depletion of circulating neutrophils, using an antineutrophil monoclonal antibody (RP3), would attenuate ischemia/reperfusion injury in rat skeletal muscle. A 3- and 5-hr period of ischemia was induced unilaterally into the hindlimbs of rats; the isolated limbs were then reperfused for 24 hr after ischemia. The gastrocnemius muscle was then removed, and blood was taken simultaneously. The hematologic parameters were measured, muscle neutrophil sequestration wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 8 publications
(9 reference statements)
0
11
0
1
Order By: Relevance
“…Recent results from our laboratory and others have shown that leukocyte recruitment in skeletal muscle varies in number and type, depending on the insult (19,28,34,46,51,52). However, there is no correlation between the number of neutrophils and the extent of collateral muscle damage.…”
Section: Discussionmentioning
confidence: 90%
“…Recent results from our laboratory and others have shown that leukocyte recruitment in skeletal muscle varies in number and type, depending on the insult (19,28,34,46,51,52). However, there is no correlation between the number of neutrophils and the extent of collateral muscle damage.…”
Section: Discussionmentioning
confidence: 90%
“…Acute respiratory distress syndrome, multiorgan failure, and death have been described as consequences of IRI [7,15]. Neutrophil activation and infiltration have been identified as primary protagonists in the pathophysiology of IRI [10,21,22]. CS results in a much greater level of metabolic strain and cellular deterioration than IRI alone, and its treatment is urgent surgical decompression by fasciotomy once identified [18,19,37,40,49].…”
Section: Discussionmentioning
confidence: 99%
“…Ainsi, dans un modèle de blessure musculaire induite par une toxine ou une infection, la suppression des neutrophiles entraîne la persistance des fibres nécrotiques [12]. La forte capacité catabolique des neutrophiles a cependant été associée égale-ment à l'induction de dommages collatéraux observés à la suite du recrutement massif de ces cellules induit par ischémie-reperfusion du tissu musculaire [13]. Les effets positifs ou négatifs des neutrophiles sur la régénération tissulaire dépendraient de leur degré d'activation qui varie selon le type et la gravité de la inflammatoire stérile (en absence d'agents infectieux) se caractérise par l'activation rapide de cellules sentinelles, suivie d'une infiltration massive et de courte durée de neutrophiles et, finalement, du recrutement de monocytes qui se différencient en macrophages [6].…”
Section: Développement De L'inflammation Et Régénération Musculaireunclassified